Sex-specific effect of dietary fatty acids on non-alcoholic fatty liver disease - Chen, Jianhua; Zhang, Zeqin; Pan, Yuning; Shi, Jiejun (Frontiers in Nutrition, 2025)
BackgroundNon-alcoholic fatty liver disease is the most common chronic hepatic disease worldwide. Dietary fatty acid is tightly associated with the development of non-alcoholic fatty liver disease but few large-scale and in-depth clinical researches have focused on the issue.MethodsWe conducted a retrospective case-control study based on the data from the 2017–2018 cycle of the National Health and Nutrition Examination Survey.ResultsA total of 2,470 adult participants were included in this study. Logistic regression analysis showed that dietary fatty acids were positively associated with non-alcoholic fatty liver disease (odds ratio and 95% confidence interval >1 and P < 0.05) except for polyunsaturated fatty acid. Subgroup analysis stratified by age stage and weight grade revealed that aforementioned association was significant only in individuals aged group 37–55 and those classified as obesity. In addition, all the fatty acid related ratios (the ratio of unsaturated fatty acids to saturated fatty acids, the ratio of polyunsaturated fatty acid to saturated fatty acid, the ratio of monounsaturated fatty acids to saturated fatty acids, the ratio of polyunsaturated fatty acids to monounsaturated fatty acids) showed protective effects against the onset and steatosis severity of non-alcoholic fatty liver disease in men, as evidenced by stratified logistic regression analysis (all the odds ratio [95% confidence interval] < 1 and P < 0.05) and smooth curve fittings.ConclusionThese findings suggest that dietary fatty acids modification could serve as a preventive strategy for male non-alcoholic fatty liver disease. Increasing the proportion of unsaturated fatty acids in the diet, especially polyunsaturated fatty acids, is promising to prevent non-alcoholic fatty liver disease in middle-aged obese men.